Determination of Shelf Life with Accelerated Shelf Life Testing (ASLT) in Beverage Seaweed - Niâ€™mah, Yatim Lailun; Suprapto, Suprapto; Ilmi, Moh. Mualliful; Agustin, Nuril Indah; Ameswari, Vennycha Dwi (IPTEK Journal of Proceedings Series, 2018)
In this research has been made beverage seaweed from main ingredient of red seaweed type Eucheuma cottonii with added other food ingredients that serve to improve the taste. In addition to labeling and commercially produced, it is necessary to determine the shelf life in seaweed beverage. Determination of shelf life of beverage seaweed was done by Accelerated Shelf Life Testing (ASLT) method. Beverage seaweed studied there are two flavors of original taste and green tea. Based on parameters of pH value, shelf life of original taste is 17 days and the taste of green tea is 34 days. The result is for storage at room temperature 30 Â°C